Pioglitazone inhibits advanced glycation induced protein modifications and down-regulates expression of RAGE and NF-kappa B in renal cells - Adeshara, Krishna A.; Agrawal, Sanskruthi B.; Gaikwad, Sushama M.; Tupe, Rashmi S. (International Journal of Biological Macromolecules, 2018)
The present work aims to determine the effect of pioglitazone on in-vitro albumin glycation and AGE-RAGE induced oxidative stress and inflammation. Bovine serum albumin was glycated by methylglyoxal in absence or presence of pioglitazone. Glycation markers (fructosamine, carbonyl groups, (l-amyloid aggregation, thiol groups, bilirubin binding capacity and AOPP); protein conformational changes (native-PAGE and HPLC analysis) were determined. Cellular study was done by estimating antioxidants, ROS levels, expression profile of membrane RAGE, NF-kappa B and levels of inflammatory cytokines (IL-6, TNF-alpha) using HEK-293 cell line. We observed that levels of glycation markers were reduced at higher concentration of pioglitazone as compared to glycated albumin. Structural analysis of glycated albumin showed inhibition of protein migration and structural changes when treated with pioglitazone. Pioglitazone has potentially restored cellular antioxidants and reduced levels of IL-6 and TNF-alpha by declining expression of membrane RAGE and NF-kappa B. In conclusion, pioglitazone preferentially binds to protein and alleviates protein structural changes by maintaining its integrity. Additionally, it suppresses RAGE and NF-kappa B levels hence alleviate cellular oxidative stress and inflammation. (C) 2018 Elsevier B.V. All rights reserved.